The People Reloaded: The Green Movement and the Struggle for Iran’s Future by Nader Hashemi & Danny Postel, eds. (Brooklyn, NY: Melville House Publishing, 2010. pbk. 462 pages) (American Journal of Islam and Society, 2011)
The People Reloaded ‒ an anthology of the multiplicity of voices, belongingto various perspectives, fields, and geographical locations throughoutthe world, and primarily and principally in the Iran and Iranian diasporas‒ is edited by Nader Hashemi (of the University of Denver) and DannyPostel (the editor of The Common Review). The book is a definitive selectedcollection of fifty-three writings and political analyses written by diverse voices interested in and engaged with the struggle for democracyin Iran. The People Reloaded is comprised of key documents, statements,interviews, letters, and essays ‒ and it seeks to capture “an important momentin Iran’s history (xxii).”This book is a rich, consistently engaging anthology that makes animportant effort to provide “an intellectual and political roadmap,” whichhelps the reader in understanding the tumultuous events that have rockedthe Islamic Republic since June 2009 ‒ a period when the struggle forthe democracy in Iran underwent a “momentous transformation (xi).” Thefacts, analyses, shadings, and nuances that these essays provide allow thereader to better understand whatever direction Iran can or may take in thefuture. The editors contribute to the work the introduction and two essays;the remaining essays are those of noted historians, political activists inand out of Iran, and journalists. Among the historians are Ervand Abrahamian,Hamid Dabashi, and Juan Cole; the activists include AyatollahMohsen Kadivar, Shirin Ebadi (2003 Nobel Peace Prize winner), and HosseinBashiriyeh; and the journalists include Roger Cohen, Stephen Kinzer,and Laura Secor. The combined effect is a history of the Green Movement,which includes much of Iran’s revolutionary past and a vision of the futureof the Green Movement in its struggle for justice and a voice in the ancientcivilization of Iran ...